Application of non-thermal plasma (NTP) for volatile compounds (VCs) removal at sewage sludge composting facility. (15th December 2022) - Mustafa, Muhammad Farooq; Abbas, Yawar; Ajmal, Muhammad; Afreen, Asma; Ahmed, Zaheer; Liu, Changli; Lu, Wenjing
Abstract: Double dielectric barrier discharge (DDBD) reactors were used to evaluate the removal efficiency of volatile compounds (VCs) from the exhaust gas of sewage sludge (SS) composting facility at optimal conditions, i.e., input power 65.8W, gas feeding rate 4 L/min, plasma discharge gap 6 mm. Abatement of VCs from different processing periods of SS composting was determined. 100% removal of major species of VCs (methyl isobutyl ketone, carbon disulfide, chlorobenzene and methylene chloride, etc.) were determined during the 'before turning (B.T)' and '5 h after turning (A.T)' process. In addition, the synergistic effect of plasma-catalyst (Pt–Sn/Al2 O3, BaTiO3 and HZSM-5) on VCs abatement showed enhanced removal performance as the formation of reactive species (H and OH radicals) was increased, especially on the surface of the catalyst. Nevertheless, plasma alone and plasma-catalyst combine systems showed the most effective reduction in odor concentration at the 'B.T' process due to low initial concentration. The study could facilitate NTP-DDBD technology application and process optimization in exhaust gases treatment of composting plants. Graphical abstract: Image 1 Highlights: Treatments of volatile compounds (VCs) mixture has been investigated in double dielectric barrier discharge (DDBD). Plasma-catalytic synergistic effect on VCs removal by introducing catalysts (Pt–Sn/Al2 O3, BaTiO3 and HZSM-5). 100% removal of major VCs species was achieved before turning (B.T) and 5 h after turning (A.T). Both plasma-alone and plasma-catalyst systems abated odor effectively at B.T.